Destination Branding Strategy Based on Innovation of Agribusiness MSME Products in Petungsewu Tourism Village - Labuda, Fitri; Suyani , Sri; Nur Anisya, Angryta (Profit: Jurnal Adminsitrasi Bisnis, 2026)
This study examines how agribusiness-based MSME product innovation can strengthen Petungsewu Village's destination branding in Dau District, Malang Regency, using a descriptive qualitative approach. Data collection was conducted through structured interviews, direct observation, and document review. Data analysis used the Miles and Huberman model, with the following stages: data collection, data reduction, data presentation, and conclusion. The results showed that agribusiness is the main basis for supporting the identity as a tourist village. Based on observations of 14 agribusiness-based MSMEs, the average product innovation was 33.2%, which is considered low. Because an approach strategy is necessary, destination branding focuses on MSME product innovation, which is the main source of brand identity. Brand equity strategy to build brand awareness. Recommendations for a model with a co-branding approach rooted in the local ecosystem, which brings together key actors, resources, and creative village activities to create a credible brand image.